Differential Transcriptional Landscape of Vero Cells During Dengue Virus 2 Infection in the Presence of Sinococuline - Amit Garg; Rahul Shukla; Amit Kumar; Charu Aggarwal; Arnab Mukhopadhyay; Navin Khanna (Microorganisms)
Dengue virus (DENV) is transmitted by Aedes genus mosquitoes and is responsible for dengue fever (DF) and other severe diseases, posing a significant challenge to the global health system. Currently, anti-dengue pharmacological treatment options are not available. Earlier, we demonstrated that Sinococuline has potent anti-dengue activity and prevents virus infection. In this study, we profile the host transcriptome response in the Vero cells after infection with DENV2 in the presence of Sinococuline, using bioinformatics to identify significant differentially expressed genes (DEGs). A total of 1510 DEGs were noted by transcriptional analysis of Vero cells that were infected with dengue virus as compared to the uninfected cells, among which 697 were upregulated and 813 were downregulated. Also, 184 out of 697 and 254 out of 817 genes were altered in dengue-infected Vero cells in the presence of Sinococuline. We found that TNF, cytokine–cytokine receptor interactions, and NF-kB signaling pathways were differentially expressed in DENV2-infected Vero cells, which was prevented by Sinococuline. The findings of this study add to our knowledge of Sinococuline’s antiviral activity in DENV2-infected Vero cells at the transcriptome level. These findings also identify potential candidate antiviral genes that can be verified for their function in the future.